Computational Science – ICCS 2022: 22nd International Conference, London, UK, June 21–23, 2022, Proceedings, Part III - Groen, Derek; de Mulatier, Clélia; Paszynski, Maciej; Krzhizhanovskaya, Valeria V; Dongarra, Jack J; Sloot, Peter M. A (Lecture Notes in Computer Science, 2022)
The four-volume set LNCS 13350, 13351, 13352, and 13353 constitutes the proceedings of the 22ndt International Conference on Computational Science, ICCS 2022, held in London, UK, in June 2022.* The total of 175 full papers and 78 short papers presented in this book set were carefully reviewed and selected from 474 submissions. 169 full and 36 short papers were accepted to the main track; 120 full and 42 short papers were accepted to the workshops/ thematic tracks. *The conference was held in a hybrid format This is an open access book.